Î²-glucanase and xylanase for beef cattle on tropical pasture - Damasceno, Matheus Leonardi; Barbizan, Mariana; Valente, Eriton Egídio Lisboa; Carvalho, Silvana Teixeira; Zoz, Kachire; Eustáquio Mesquita, Eduardo; Lopes, Sidnei Antônio; Carvalho, Victor Valério (Semina: Ciências Agrárias, 2024)
The aim of this study was to assess the impact of administering an energy-protein supplement with fibrolytic enzymes, either singly or in a blend, on the intake, digestibility, ruminal, and metabolic parameters in grazing beef cattle. Five rumen-cannulated Nellore steers, averaging 36 months of age and a body weight of 559.57 Â± 35 kg were evaluated using a 5 x 5 Latin Square design. The treatments included a protein-energy supplement (2 g/kg BW) without additives (Control), or supplemented with 4 g Î²-glucanase/animal (BGLU); 4 g xylanase/animal (XYLA); 4 g Î²-glucanase and 1 g xylanase/animal (BGLU+XYLA); and 4 g xylanase and 1 g Î²-glucanase/animal (XYLA+BGLU). The administration of either single fibrolytic enzymes or the enzyme blend did not significantly influence (P > 0.05) the intakes of forage dry matter (DM), total DM, crude protein (CP), neutral detergent fiber (NDF), organic matter (OM), digestible OM, or the digestibility coefficients of DM, NDF, CP, and OM. Similarly, the use of these enzymes individually or combined did not impact (P > 0.05) the levels of rumen pH, volatile fatty acids, ruminal ammonia nitrogen, microbial nitrogen, serum urea nitrogen, or urinary nitrogen excretion. Providing fibrolytic enzymes, individually or in blends, does not modify the nutrient intake, digestibility, or metabolism in beef cattle on tropical pastures receiving low levels of protein-energy supplements.